An Unusual Cause of Secondary ITP in a 34-Year-Old Hispanic Male - Ayrton Bangolo; Mohamed Ahmed; Ali Atoot; Ashraf Mahmoud; Chibuzo Agbakwuru-Onyike; Maria Karina Larni Y. Palad; Michael Sciarra; Adam Atoot (Case Reports in Hematology)
Secondary immune thrombocytopenic purpura (ITP) associated with Helicobacter pylori (H. pylori) infection has been described in the literature. It appears to have a geographic distribution; mostly encountered in countries with a higher prevalence for H. pylori such as Italy or Japan. H. pylori eradication has been recommended in the management of ITP with studies showing improvement in the platelet count in some patients. Substantial platelet count increases in patients with severe thrombocytopenia (platelet counts <30 × 103 microliter), however, are uncommon with H. pylori treatment alone. Here, we present a 34-year-old Hispanic male with worsening chronic thrombocytopenia that resolved following eradication of his H. pylori infection. Herein, we highlight a rare and reversible cause of secondary ITP. With this case report, we hope to encourage physicians to include H. pylori testing in the evaluation of thrombocytopenia.